Vitalism Revitalized: Vulnerable Populations, Prejudice, and Physician-Assisted Death - Mayo, David J. (The Hastings Center report, 2002)
One of the most potent arguments against physician-assisted death hinges on the worry that people with disabilities will be subtly coerced to accept death prematurely. The argument is flawed. There is nothing new in PAD: the risk of coercion is already present in current policies about end of life care. And to hold that any such risk is too much is tacitly to endorse vitalism and to deny that people with disabilities are capable of choosing authentically.